The Antibacterial Potential of Ethanol Extracts of Torch Ginger Leaves (Etlingera elatior (Jack) R.M.Sm.) Against Enterococcus faecalis as an Alternative Irrigation Material in Root Canal Treatment - Amalia Bachtiar, Zulfi; Luthfiani, Luthfiani; Muthmainnah, Inna; Putra Manurung, Supredo (Jurnal Kesehatan Gigi, 2024)
Root canal infection is a polymicrobial infection that is a progression of chronic caries affecting the dental nerve tissue and surrounding root tissue, which can be accompanied by extremely uncomfortable sharp pain. Enterococcus faecalis is one of the infecting agents that can be found in primary root canals experiencing endodontic infections and is resistant to root canal irrigation materials, thus leading to root canal treatment failure. Herbal plants have been used since ancient times by the Indonesian people to address health issues due to the believed beneficial properties of their constituents. Research on torch ginger reports pharmacological activities such as antimicrobial, antioxidant, anti-inflammatory, anticancer, and anti-aging effects. Torch ginger (E. elatior) is a spice plant reported to have antibacterial bioactive compounds. This study aims to determine the antibacterial activity of ethanol extract from torch ginger leaves (E. elatior) against Enterococcus faecalis bacteria. The Kirby-Bauer disk diffusion method was used to determine the minimum inhibitory concentration (MIC) value and the streaking method from MIC testing to determine the minimum bactericidal concentration (MBC) with 8 concentrations and 2 controls. Data analysis of the MIC and MBC values was performed using One-Way ANOVA and Kruskal-Wallis parametric tests. The ethanol extract of torch ginger leaves (E. elatior) has minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values against Enterococcus faecalis bacteria. The minimum inhibitory concentration of the ethanol extract of torch ginger leaves is at a concentration of 3.125%, while the minimum bactericidal concentration is at a concentration of 65%.